Assessing the factorial validity and longitudinal invariance of indicators of basic early reading skills in Spanish first graders - Jiménez, Juan E.; García, Eduardo (Anales de Psicología / Annals of Psychology, 2025)
A study was conducted to analyze the factor validity and longitudinal measurement invariance of indicators of basic early reading skills in Spanish first-grade students, using a curriculum-based measurement (CBM) approach. The proposed model is a bifactor model comprising two correlated factors: one factor, comprised of tasks measuring alphabetic knowledge, phonological awareness, and print awareness, serves as observable indicators for the foundational skills underlying factor; while oral reading fluency, pseudoword reading, and maze sentences serve as observable indicators of the conventional literacy or reading skills factor. The CBM consisted of three parallel forms (A, B, and C) and was administered at three different times during the school year (fall, winter, spring) to 947 Spanish first-grade students. It is concluded that the CBM demonstrates adequate construct validity and measurement equivalence, allowing for the evaluation of first-grade essential skills occurring as children learn to read.